P21-activated kinase 1 (PAK1) as a therapeutic target in BRAF wild-type melanoma. - Ong, C; Jubb, A; Jakubiak, D; Zhou, W; Rudolph, J; Haverty, P; Kowanetz, M; Yan, Y; Tremayne, J; Lisle, R; Harris, A; Friedman, L; et al. (2013)
BACKGROUND: Although remarkable clinical response rates in melanoma have been observed using vemurafenib or dabrafenib in patients with tumors carrying oncogenic mutations in BRAF, a substantial unmet medical need remains for the subset of patients with wild-type BRAF tumors. METHODS: To investigate the role of p21-activated kinases (PAKs) in melanoma, we determined PAK1 genomic copy number and protein expression for a panel of human melanoma tissues. PAK1 was inhibited in vitro and in vivo using RNA interference or PF-3758309 inhibitor treatment in a panel of melanoma cell lines with known BRAF and RAS (rat sarcoma) genotype to better understand its role in melanoma cell proliferation and migration. Tumorigenesis was assessed in vivo in female NCR nude mice and analyzed with cubic spline regression and area under the curve analyses. All statistical tests were two-sided. RESULTS: Strong cytoplasmic PAK1 protein expression was prevalent in melanomas (27%) and negatively associated with activating mutation of the BRAF oncogene (P < .001). Focal copy number gain of PAK1 at 11q13 was also observed in 9% of melanomas (n = 87; copy number ≥ 2.5) and was mutually exclusive with BRAF mutation (P < .005). Selective PAK1 inhibition attenuated signaling through mitogen-activated protein kinase (MAPK) as well as cytoskeleton-regulating pathways to modulate the proliferation and migration of BRAF wild-type melanoma cells. Treatment of BRAF wild-type melanomas with PF-3758309 PAK inhibitor decreased tumor growth for SK-MEL23 and 537MEL xenografts (91% and 63% inhibition, respectively; P < .001) and MAPK pathway activation in vivo. CONCLUSIONS: Taken together, our results provide evidence for a functional role of PAK1 in BRAF wild-type melanoma and therapeutic use of PAK inhibitors in this indication.